2011
DOI: 10.1111/j.1600-0528.2011.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Are mental health problems and depression associated with bruxism in children?

Abstract: Renner AC, da Silva AAM, Rodriguez JDM, Simões VMF, Barbieri MA, Bettiol H, Thomaz EBAF, Saraiva MC. Are mental health problems and depression associated with bruxism in children? Community Dent Oral Epidemiol 2011. © 2011 John Wiley & Sons A/S Abstract –  Objectives:  Previous studies have found an association between bruxism and emotional and behavioral problems in children, but reported data are inconsistent. The objective of this study was to estimate the prevalence of bruxism, and of its components clench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
2
22

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 31 publications
8
47
2
22
Order By: Relevance
“…However, among pre-school and first grade children, the higher frequencies of sleep-bruxism (e.g., more than four times a week) were congruent with values previously reported (e.g., [1,[8][9][10]). Notably, sleep-bruxism distinction and frequency is not equivalently described in all studies; thus, many epidemiological studies on sleep bruxism are not fully comparable.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, among pre-school and first grade children, the higher frequencies of sleep-bruxism (e.g., more than four times a week) were congruent with values previously reported (e.g., [1,[8][9][10]). Notably, sleep-bruxism distinction and frequency is not equivalently described in all studies; thus, many epidemiological studies on sleep bruxism are not fully comparable.…”
Section: Discussionsupporting
confidence: 80%
“…The reported prevalence of sleepbruxism is highest during childhood, decreases across the life span and can resolve spontaneously [7]. The prevalence of childhood sleep-bruxism varies from 14% to 17% [1], 5-20% [8], 22% [9], 28-30% [10], and 38% [11]; however, prevalence rates may be underestimates since less common occurrences may not come to medical attention [12]. The reported prevalence of child sleep-bruxism ranges widely; large community-based samples of children could help clarify prevalence rates.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed, at least partially, to differences in the questionnaires used. The authors observed great variation in the questions, for example: single-item or part of sleep behavior questionnaires 20,21 , frequency-time 22,23 or general question 24 , and some studies included in this systematic review had unspecified questions 25 . In this study, the GQ does not distinguish between wake-time and sleep bruxism, unlike the FTQ, which was more specific with respect to the moment of the events.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of an association between bruxism and tension, stress, and emotional disturbance, corroborating this idea. 22 Therefore, special attention should be paid to children with a habit of finger sucking during infancy to prevent a future occurrence of other DOH.…”
Section: Discussionmentioning
confidence: 99%